CHECKLIST DE CHIRONOMIDAE (INSECTA, DIPTERA) EM ÁREAS DE CONSERVAÇÃO DE PERNAMBUCO, BRASIL - Nascimento, Carlos Henrique de Vasconcelos; Santos, Iris Gabrielly Arruda dos; Silva, Fábio Laurindo da; Rodrigues, Gilberto Gonçalves (Revista Nordestina de Zoologia, 2016)
The objective of the study was to perform a checklist of the Chironomidae in three protected areas in Pernambuco, since there are still few studies for the northeast region. The larvae were collected with hand and by leaf colonization (litterbags), and adult specimens were collected with a light trap, for molecular identification performed according to DNA barcode technique. Thirty-three Chironomidae taxa were identified, distributed in 20 genera of the Chironomini tribe, nine genera of the Tanypodini tribe, three of the Tanytarsini tribe and one genus of the Orthocladinae tribe. Most taxa are new records for Pernambuco.